2015
DOI: 10.1017/thg.2015.82
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Replacement Therapy Associated White Blood Cell DNA Methylation and Gene Expression are Associated With Within-Pair Differences of Body Adiposity and Bone Mass

Abstract: The loss of estrogen during menopause causes changes in the female body with wide-range effects on health. Estrogen-containing hormone replacement therapy (HRT) leads to a relief of typical menopausal symptoms, benefits bone and muscle health, and associates with tissue-specific gene expression profiles. As gene expression is controlled by epigenetic factors (including DNA methylation) many of which are environmentally sensitive, it is plausible that at least part of the HRT-associated gene expression is due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 64 publications
(88 reference statements)
1
18
0
Order By: Relevance
“…The circulating miRs showing differential expression due to use of HRT were associated with apoptosis, inflammation and body metabolic pathways (Kangas et al, 2014;Kangas, Morsiani et al, 2017). These results are in line with our previous results indicating that the use of HRT affects muscle signaling at transcriptome (Ronkainen et al, 2010) and proteome (Laakkonen et al, 2017) levels, as well as white blood cell signaling at methylome and transcriptome levels (Bahl et al, 2015).…”
Section: Estrogen and Sarcopenia: A Co-twin Study With Hrt Discordantsupporting
confidence: 90%
“…The circulating miRs showing differential expression due to use of HRT were associated with apoptosis, inflammation and body metabolic pathways (Kangas et al, 2014;Kangas, Morsiani et al, 2017). These results are in line with our previous results indicating that the use of HRT affects muscle signaling at transcriptome (Ronkainen et al, 2010) and proteome (Laakkonen et al, 2017) levels, as well as white blood cell signaling at methylome and transcriptome levels (Bahl et al, 2015).…”
Section: Estrogen and Sarcopenia: A Co-twin Study With Hrt Discordantsupporting
confidence: 90%
“…Even though no direct effect of E 2 has been stated in the mentioned studies, it has been well demonstrated that estrogen has a role as a neuro-, osteo- and vascular protector 28 29 30 31 . Our earlier studies have also shown beneficial effects of postmenopausal HRT on body composition measures, including fat, muscle and bone properties 32 33 34 35 36 . The connection between lipoproteins, vascular inflammation and exosomes has also been recognized by others 37 .…”
Section: Discussionmentioning
confidence: 77%
“…HRT was found to affect the body composition in healthy elders, but at least part of the known beneficial HRT effects on body composition and bone mass may be regulated by DNA methylation associated alterations in gene expression in circulating white blood cells16. The effect of HRT on the body composition in patients with TS remains unclear.…”
Section: Discussionmentioning
confidence: 99%